2015
DOI: 10.1007/s40472-014-0046-1
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic Oxygenated Liver Perfusion: Basic Mechanisms and Clinical Application

Abstract: Dynamic preservation strategies such as hypothermic machine perfusion are increasingly discussed to improve liver graft quality before transplantation. This review summarizes current knowledge of this perfusion technique for liver preservation. We discuss optimization of perfusion conditions and current strategies to assess graft quality during cold perfusion. Next, we provide an overview of possible pathways of protection from ischemia-reperfusion injury. Finally, we report on recent clinical applications of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 86 publications
1
69
0
Order By: Relevance
“…10 Our study demonstrates that HOPE prevents oxidative stress or DAMPs release during perfusion. 8,10,24 In addition, HOPE treatment prevents mitochondrial ROS production and downstream macrophage and endothelial activation during reperfusion, 8,29 potentially by a reversible downregulation of mitochondrial electron transfer. 8 Accordingly, kidney grafts treated by HOPE showed significant less TLR-4-positive cells, less TNF-a release, less endothelial cell activation after implantation, and were rescued from lethal injury, in contrast to normothermic perfusion or cold storage alone.…”
Section: Discussionmentioning
confidence: 99%
“…10 Our study demonstrates that HOPE prevents oxidative stress or DAMPs release during perfusion. 8,10,24 In addition, HOPE treatment prevents mitochondrial ROS production and downstream macrophage and endothelial activation during reperfusion, 8,29 potentially by a reversible downregulation of mitochondrial electron transfer. 8 Accordingly, kidney grafts treated by HOPE showed significant less TLR-4-positive cells, less TNF-a release, less endothelial cell activation after implantation, and were rescued from lethal injury, in contrast to normothermic perfusion or cold storage alone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work, however, confirmed that hypothermic liver perfusion with completely deoxygenated perfusate failed to protect from reperfusion injury [22,29 & ]. Of note, the rate of oxygen consumption during HOPE is not stable but decreases rapidly during the first hour, and ceases after 90 min at a low baseline level [13,22,34]. This effect relates to a decrease of electron-rich substrates during hypothermic oxygenation [22].…”
Section: Oxygenmentioning
confidence: 97%
“…Therefore, the concept of machine perfusion instead of conventional static cold storage has been nowadays revisited to improve graft viability [12]. The concurring machine perfusion strategies for livers differ in perfusate conditions, including particularly temperature and timing of perfusion [13,14]. In this review, we summarize recent developments in the field of hypothermic machine liver perfusion, and focus on clinical application in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygenated machine perfusion has many advantages over hypothermic machine perfusion. It can protect liver grafts exposed to warm and cold ischemia [44] and can efficiently deliver nutrients and oxygen into the core of the organ under appropriate conditions. The extracorporeal membrane oxygenation technology has been used sporadically in controlled DCD donors under normothermic [45,46] and subnormothermic [47] conditions.…”
Section: Discussionmentioning
confidence: 99%